1998
DOI: 10.1017/s0033291797006041
|View full text |Cite
|
Sign up to set email alerts
|

Executive function in first-episode schizophrenia

Abstract: Background. We tested the hypothesis that schizophrenia is primarily a frontostriatal disorder by examining executive function in first-episode patients. Previous studies have shown either equal decrements in many cognitive domains or specific deficits in memory. Such studies have grouped test results or have used few executive measures, thus, possibly losing information. We, therefore, measured a range of executive ability with tests known to be sensitive to frontal lobe function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
160
0
15

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(196 citation statements)
references
References 46 publications
19
160
0
15
Order By: Relevance
“…WM deficits show minimal cross-sectional correlations with severity of delusions and hallucinations, are detectable in clinically stabilized outpatients, and appear to be relatively stable across both time and fluctuations in clinical status, suggesting that they are not merely secondary manifestations of psychotic symptoms Hill et al 2004;Park et al 1999). They are also not secondary to antipsychotic medication side effects or factors associated with chronicity, as deficits of comparable magnitude are present in neuroleptic-free patients (Barch et al 2001;Carter et al 1996) and during the immediate post-onset period (Hutton et al 1998;Lussier and Stip 2001).…”
Section: Introductionmentioning
confidence: 99%
“…WM deficits show minimal cross-sectional correlations with severity of delusions and hallucinations, are detectable in clinically stabilized outpatients, and appear to be relatively stable across both time and fluctuations in clinical status, suggesting that they are not merely secondary manifestations of psychotic symptoms Hill et al 2004;Park et al 1999). They are also not secondary to antipsychotic medication side effects or factors associated with chronicity, as deficits of comparable magnitude are present in neuroleptic-free patients (Barch et al 2001;Carter et al 1996) and during the immediate post-onset period (Hutton et al 1998;Lussier and Stip 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well-documented deficits in PPI and P50 suppression, the occurrence of impaired cognitive performance, especially working memory, is a robust finding in schizophrenia patients (Hutton et al, 1998;Weickert et al, 2000;Badcock et al, 2005). Moreover, it has recently been demonstrated that those healthy human volunteers exhibiting low levels of PPI also show impaired performance in specific cognitive tasks relying on prefrontal cortical functioning Bitsios et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Stockings of Cambridge (SOC ; computerized version of Tower of London) task assesses planning and thinking and is thought to involve the dorsolateral prefrontal cortex. Patients with schizophrenia typically make fewer perfect solutions and more moves on the SOC task (Pantelis et al 1997 ;Elliott et al 1998 ;Hutton et al 1998 ;Tyson et al 2004 ;Braw et al 2008). The Cambridge Gamble Task (CGT) of decision making and impulsivity is sensitive to the integrity of orbitofrontal neuro-circuitry (Rahman et al 1999 ;Rogers et al 1999 ;Murphy et al 2001).…”
Section: Introductionmentioning
confidence: 99%